The Formation of the International Coalition Against ISIS and its Main Challenges Front (2014-2017) - Abdullah دلۆڤان; Issa صالح (Zanco Journal of Law and Politics گۆڤاری زانكۆ بۆ یاساو رامیاری, 2025)
The rise of the terrorist group ISIL in 2014 and its rapid expansion and occupation of a significant part of Iraq and Syria, posed a serious threat to regional and global security. In response to this crisis, a US-led international military coalition was formed to fight ISIS. This article follows the process of forming this coalition between 2014 and 2017 and tries to analyze the process, objectives and challenges of legal, strategic and political importance and explain the answers to these questions: What were the problems facing the formation of this coalition? And have they affected the main goal, the fight against terrorism? Finally, the study concludes that despite the relative success in weakening the military structure of ISIS, but the structural and political problems of members and other countries involved in the fight against terrorism remain a major obstacle to a continuous fight against international terrorism has collected by the subject.